Drug Delivery Systems for Imaging and Therapy of Parkinson's Disease - Gunay, Mine Silindir (Curr Neuropharmacol, 2016)
Background: Although a variety of therapeutic approaches are available for the treatment of Parkinson’s disease, challenges limit effective therapy. Among these challenges are delivery of drugs through the blood brain barier to the target brain tissue and the side effects observed during long term administration of antiparkinsonian drugs. The use of drug delivery systems such as liposomes, niosomes, micelles, nanoparticles, nanocapsules, gold nanoparticles, microspheres, microcapsules, nanobubbles, microbubbles and dendrimers is being investigated for diagnosis and therapy. Methods: This review focuses on formulation, development and advantages of nanosized drug delivery systems which can penetrate the central nervous system for the therapy and/or diagnosis of PD, and highlights future nanotechnological approaches. Results: It is esential to deliver a sufficient amount of either therapeutic or radiocontrast agents to the brain in order to provide the best possible efficacy or imaging without undesired degradation of the agent. Current treatments focus on motor symptoms, but these treatments generally do not deal with modifying the course of Parkinson’s disease. Beyond pharmacological therapy, the identification of abnormal proteins such as α-synuclein, parkin or leucine-rich repeat serine/threonine protein kinase 2 could represent promising alternative targets for molecular imaging and therapy of Parkinson's disease. Conclusion: Nanotechnology and nanosized drug delivery systems are being investigated intensely and could have potential effect for Parkinson’s disease. The improvement of drug delivery systems could dramatically enhance the effectiveness of Parkinson’s Disease therapy and reduce its side effects.